Effect of isometric handgrip exercise on blood pressure and comfort among hypertensive patients - Veralia, Veralia; Malini, Hema; Gusty, Reni Prima (Jurnal Ners, 2023)
Introduction: Hypertension patients with uncontrolled blood pressure will experience some physical complaints. Controlled blood pressure will reduce physical complaints and improve comfort. Physical activity can help in making blood pressure controlled. However, due to limited time and access, many hypertensive patients rarely do some exercise. This study aimed to investigate the Isometric Handgrip Exercise's effect on blood pressure and comfort of hypertension patients. Methods: The research design is a quasi-experimental pre and post-test with the control group. The population was hypertension patients who were members of the chronic program disease, had hypertension pre and grade 1, and no further complication or physical impairment. The sample used unpaired numerical analytical formulas, obtained by 25 patients for each group. The intervention of an Isometric Handgrip was conducted for ten days. In one day, there is one session with 4x3 minutes. Results: The results showed a significant relationship between isometric handgrip exercise with a decrease in blood pressure and increased patient comfort. Conclusions: Isometric handgrip exercise can be an alternative activity for patients that influences helping to maintain stable blood pressure and reduce the physical discomfort